PEMBINAAN GURU MELALUI SUPERVISI AKADEMIK UNTUK MENINGKATKAN MUTU PEMBELAJARAN RAUDHATUL ATHFAL - Entin Kartini (JENTRE, 2021)
The competence of Raudhatul Athfal (RA) teachers in preparing Weekly Learning Implementation Plan (RPPM) and Daily Learning Implementation Plan (RPPH) is still not maximized. Their understanding on RPPM and RPPH’s preparation is still low. The learning has not been structured, detailed, traced based on the latest curriculum development, i.e. revised 2013 RA curriculum. Through executing academic supervision, it is expected that teachers will be able to prepare RPPM and RPPH. The main duties and functions of supervisors include coaching teachers in form of academic supervision which supports learning process implementation. Through academic supervision process, teachers are fostered to be ready preparing RPPM and RPPH in accordance with 2013 curriculum systematics, so that the learning quality increases. The supervision was carried out in Cibeunying District, Bandung, with a total of 20 (twenty) teachers. Participation activeness in teachers’ training is 87.5% (high) to 97.5% (very high) increased by 8%, cooperation in groups is initially from 90% (high) to 97.5% (very high), 6% increased, and the percentage of courage to create presentation is from 85% (high) to 95% (very high), raised 8%. In the second cycle, the teacher's mastery on RPPM and RPPH’s consisting of opening lesson, learning method/models, and closing lessonn/evaluation has increased. To sum up the research of academic supervision, both teacher competence in RPPM and RPPH’s preparation as well as learning quality have been developed.